Antibiotic Prophylaxis for Preventing Surgical-Site Infection in Plastic Surgery: An Evidence-Based Consensus Conference Statement from the American Association of Plastic Surgeons. Issue 6 (June 2015) - Ariyan, Stephan; Martin, Janet; Lal, Avtar; Cheng, Davy; Borah, Gregory L.; Chung, Kevin C.; Conly, John; Havlik, Robert; Lee, W. P. Andrew; McGrath, Mary H.; Pribaz, Julian; Young, V. Leroy
Abstract : Background: There is a growing concern for microbial resistance as a result of overuse of antibiotics. Although guidelines have focused on the use of antibiotics for surgery in general, few have addressed plastic surgery specifically. The objective of this expert consensus conference was to evaluate the evidence for efficacy and safety of antibiotic prophylaxis in plastic surgical procedures. Methods: The authors: searched for existing high-quality systematic reviews for antibiotic prophylaxis in the literature from the MEDLINE, Cochrane Library, and Embase databases. All synonyms for antibiotics were combined with terms for relevant plastic surgery procedures. The searches were not limited by language, and included all study designs. In addition, supplemental hand searches were performed of bibliographies of relevant articles, and extensive "related articles." Meta-analyses were performed and reviewed by experts selected by the American Association of Plastic Surgeons to reach consensus recommendations. Results: Database searches identified 4300 articles, from which 2042 full-text articles were identified for eligibility. De novo meta-analyses were performed for each plastic surgical category. In total, 67 studies met the inclusion criteria, including nine for breast surgery, 17 for head and neck surgery, 10 for orthognathic surgery, seven for rhinoplasty/septoplasty, 19 for hand surgery, five for skin surgery, and two for abdominoplasty. Conclusions: Systemic antibiotic prophylaxis is recommended for clean breast surgery and for contaminated surgery of the hand or the head and neck. It is not recommended to reduce infection in clean surgical cases of the hand, skin, head and neck, or abdominoplasty.